2018
DOI: 10.1080/14767058.2018.1462321
|View full text |Cite
|
Sign up to set email alerts
|

The inferior vena cava diameter is a useful ultrasound finding for predicting postpartum blood loss

Abstract: The ultrasonographic measurement of the IVC diameter was found to be the most useful parameter in evaluating the actual maternal blood loss after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
4
16
1
2
Order By: Relevance
“…Other methods for the intraoperative recording of blood loss are rarely described and have not yet been sufficiently tested. Ultrasound of the inferior vena cava [20,84,85], contrast enhanced ultrasound (CEUS) [86], hemodynamic esophageal Doppler monitoring [19], near-infrared spectroscopy [87] or continuous non-invasive intraoperative Hb monitoring [23,88,89] for intraoperative detection of blood loss have been investigated. None of these methods represents a valid technique for blood loss detection.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods for the intraoperative recording of blood loss are rarely described and have not yet been sufficiently tested. Ultrasound of the inferior vena cava [20,84,85], contrast enhanced ultrasound (CEUS) [86], hemodynamic esophageal Doppler monitoring [19], near-infrared spectroscopy [87] or continuous non-invasive intraoperative Hb monitoring [23,88,89] for intraoperative detection of blood loss have been investigated. None of these methods represents a valid technique for blood loss detection.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…The risk of bias due to confounders was increased in the majority of the studies. The selection of participants in study groups showed an increased risk of bias in four studies [19][20][21][22] and an unclear risk of bias in two studies [23,24]. The documentation and endpoint assessment were adequately described in most of the studies.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…21 Tomohiro et al found that the ultrasonographic measurement of the IVC diameter was a more accurate marker than vital parameters in predicting serious anemia after birth and identifying patients who will require blood transfusions. 11 On the other hand, Sefidbakht et al 12 and Yanagawa et al 13 showed that the rapid ultrasound performed for bedside IVC evaluation was more sensitive than blood pressure in assessing fluid loss in patients presenting in the emergency department for various types of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Many studies have been conducted to determine the fluid deficit with the help of the IVC diameter and collapsibility index (CI) in the postpartum period, in trauma, cardiogenic-hypovolemic and septic shock patients. [11][12][13] However, to our knowledge, there is no study evaluating preoperative intravascular volume with IVC diameter and CI in the pediatric patient group. Therefore, this study was designed to evaluate changes in IVC diameter and CI of the restriction of preoperative oral nutrition in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…В дальнейшем T. Oba и соавт. [45] продолжили работу по изучению диаметра нижней полой вены в качестве предиктора тяжелой анемии (уровень гемоглобина ≤70 г/л на следующие сутки после родов) при вагинальных родах с кровопотерей ≥500 мл и сравнению с другими параметрами, такими как АШИ, САД, ЧСС. Итогом проведенной работы стал вывод, что диаметр нижней полой вены обладал наибольшей чувствительностью и был наиболее полезным параметром фактической оценки кровопотери после родов [45].…”
unclassified